A Bibliometric Analysis of Nanocrystalline Cellulose Production Research as Drug Delivery System Using VOSviewer - Allifya Fauziah (Universitas Pendidikan Indonesia (UPI), 2022)
Nanocrystalline cellulose (NCC) has a superiority due to its biocompatibility and biodegradability whose increases the interest of researchers in the field of nanotechnology, especially in drug delivery systems. The purpose of this study is to conduct bibliographical analysis in nanocrystalline cellulose production and its application as a drug delivery system, that combines mapping analysis with VOSviewer software. The reference manager application was used to retrieve survey data. The data obtained is the result of searching for the keyword